Bibliometric Computational Mapping Analysis of Learning Video in Beauty Field (Vocational High School & University) Using VosViewer - Chairani, Vici Syahril (AI Society & STMIK Indonesia, 2023)
This study aims to analyze the use of learning videos in Beauty Vocational Schools and Beauty study programs at the University level between 2013 and 2023 using bibliometric computational mapping analysis methods. Publish or Perish (PoP) software was used to collect publication data from the Google Scholar database using the keywords